Sargodha High: A Flexure Forebulge of the Himalayan Foreland Basin - Irfan, Muhammad; Shahid, Muhammad; Haroon, Muhammad; Zaidi, Nazar Abass (Journal of Himalayan Earth Sciences, 2005)
Foreland basins are characterized by down warps due to orogenic overloading and flexure forebulge at the periphery. The uplifting and shifting of flexure bulge results in the erosion of sediments and ultimately presence of unconformity in the stratigraphic record. Interpretation of seismic and geological data reveals that Sargodha High is a flexure bulge of the Himalayan foreland basin and has resulted Oligocene hiatus in the stratigraphic record. The stratigraphic gap at the base of Neogene mollase results from erosion of the former passive margin series during the Oligocene, but also from the progressive onlap of Miocene flexural series towards the foreland bulge. The proper identification of flexure forebulge unconformity aids in predicting petroleum play system in the enclosing sediments.